EFEK HYPOGLIKEMIK EKSTRAK ALKOHOL HERBA MENIRAN (Phyllanthus niruri L.) PADA KELINCI PUTIH JANTAN - Chairul, Chairul; Jamal, Yuliasri; Zainul, Zuherti (BERITA BIOLOGI, 2000)
A study on the influences of alcohol extract of Meniran or Phyllanthus niruri L. (Euphorbiaceae) to blood glucose concentration in rabbits (Oxytolagus cuniculus) had been carried out using glucose tolerance method.The extract was administered orally at 10, 20, 30, 40 and 50 mg/kg BW.Prior to tfie extract administration, all rabbits were put on hyperglycemic condition by injecting glucose solution intravenally at dose of 0.5 g/kg BW.The blood glucose concentration was measured every one hour starting at 2 hours before and until 7 hours after administration. Antidiabetic drug,tolbutamid 250 mg/kgBW.was used as control.The results indicated that extract with dose at 30 mg/kg BW gave a hypoglycemic effect similar to control (Tolbutamid). The blood glucose decreased regularly as the extract dose being higher.Using statistical analyses showed significant differences among the groups, especially after the 2 and 3 hours of treatment (P<0.05).